Religion and the moral being of man: a critical analysis on Said Nursi's thought and its relevance in addressing the postmodern claims against religious morality - Awang Abd Rahman, Amilah (2021)
Nursi is a renowned scholar for his idea of reform who addressed to various challenges of the modernism. This paper aims at exploring “The Short Words” and its relevance to respond to the challenge of postmodern nihilism. With the latest developments in human life, ideas on postmodernism receive more attention and has been a threat to religions especially Islam. To achieve the aim, the paper analyses Nursi’s point of views in his epistles known as the Short Words which highlights the meaning of religion in life and the meaning of moral being. It later explores the stance of postmodernism on the role religion in morality and the status of man as a moral being with special focus on Nietzsche’s view. Nursi offers balanced arguments and justification for the meaning of true faith. Instead of limiting man’s freedom and choice, the true faith boosts the spirit of ideal morality in man. Not only Nursi is successful in refuting the false understanding of postmodern thinkers towards religion, but also his notion of true faith as presented in allegorical stories can be the answer to the quest for a proper system in enhancing the achievement of individual moral excellence.